Examining the Challenges that hinder the development of entrepreneurship skills among secondary school students in Zimbabwe: - Chinokopota, Tabeth; Ngorora-Madzimure, Grace Portia Kuda; Msipa, Nothando; Bhebhe, Thomas Brighton (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: The purpose of this study was to examine the challenges that are faced by schools in developing entrepreneurship skills among learners in order to achieve a sustainable education system in Zimbabwe with special focus on secondary schools in Mashonaland West Province. Design/methodology/approach: Data were collected through face-to-face interviews and focus group discussions as this study was qualitative in nature. Teachers and ‘A’ level students were the respondents while School Heads and Education Officers were the key informants. The thematic analysis approach was used to analyse and present data. Findings: The study established that various challenges are encountered by secondary schools in attempting to develop entrepreneurial skills among students. Most such challenges emanate from lack of entrepreneurially qualified teachers to deliver practical entrepreneurship skills to secondary school students, lack of financial and material resources to start entrepreneurial projects and the curricula not favouring entrepreneurship skills development. The study further noted that lack of electricity in rural areas and general negative attitudes by students who think that buying, selling and producing are a sign of desperation are some of the challenges that hinder entrepreneurial skills development. Practical implications: The study recommended that financial and material resources be made available to construct physical infrastructure for start-up entrepreneurial projects. The study further recommends installation of electricity in all rural secondary schools as an enabler for students and teachers to widen their choices of entrepreneurial projects and help them access internet. Entrepreneurship training of both students and teachers and career guidance so that students change their mind-sets, attitudes and negative perceptions of entrepreneurship is also a necessity. Paper type: Research paper.